Victim or Villain? A Study of Deconstruction in Tiara Andini’s ‘Maafkan Aku’ - Meria Zakiyah Alfisuma; Eka Susylowati; M. Masqotul Imam Romadlani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study applies deconstruction, a key theory in postcolonial studies, to analyze and reinterpret the meaning within Tiara Andini's popular Indonesian song, Maafkan Aku. By examining both the literal meaning and its deconstruction, the research aims to uncover hidden layers of meaning in the song's lyrics. Using a descriptive qualitative approach, data from the lyrics are analyzed through textual analysis and the concept of deconstruction. The analysis first identifies binary oppositions in the lyrics and then challenges these oppositions to reveal new interpretations. Findings highlight the contrast between themes of penitence (as the song’s explicit meaning) and expectation (as its underlying meaning). The lyrics deconstruct the notion of penitence as a